Effect of surface roughness on surface free energy of coated papers - Kaplanová, Marie; Vališ, Jan; Jašúrek, Bohumil; Syrový, Tomáš (University of Pardubice, 2011)
The surface properties of two sets of coated printing papers were studied by the monitoring of the dynamic behaviour of small drop of standard liquid (water, ethylene glycol, formamide and methylene iodide) in time region of 20 s after drop impact on solid surface (“sessile“ drop method). The contact angle 2 formed by a liquid drop at the three-phase boundary is a quantitative measure of the wetting of a solid by a liquid. The usual goal of the contact angle measurement is the calculation of surface free energy (SFE) of solid using the semi-empirical equations including the estimation of the interfacial interaction between liquid and solid phases. Using the “cos 2 model”, pseudo-equilibrium contact angle 2 eq, liquid spreading rate k1 and the rate of liquid penetration k2 were evaluated. Surface roughness was measured by profilometer and by instrument Parker Print- Surf TM. The roughness values obtained by both methods correlated well. The spreading rate parameter k1 decreases and the k2 parameter increases with increasing roughness of tested papers. The topographical structure of paper samples was studied by electron microscopy. Polar and disperse components of SFE were evaluated by means of different theoretical approaches to interphase interactions (Owens–Wendt, van Oss, Good and Chaudhury and Wu). The SFE calculation based on Owens–Wendt and Wu equations resulted in much higher values of the total SFE and its polar component than the values calculated by acido-basic approach derived by van Oss et al.